Testing the molecular nature of the $$Ω (2012)$$ Ω ( 2012 ) with the $$ψ (3770) → \bar{Ω } \bar{K} Ξ $$ ψ ( 3770 ) → Ω ¯ K ¯ Ξ and $$ψ (3770) → \bar{Ω } \bar{K} Ξ ^*(1530) (\bar{Ω } \bar{K} π Ξ )$$ ψ ( 3770 ) → Ω ¯ K ¯ Ξ ∗ ( 1530 ) ( Ω ¯ K ¯ π Ξ ) reactions - Jing Song; Wei-Hong Liang; Chu-Wen Xiao; Jorgivan Morais Dias; Eulogio Oset (European Physical Journal C: Particles and Fields)
Abstract We report on the reactions $$ψ (3770)→ \bar{Ω }^+ \bar{K} Ξ $$ ψ ( 3770 ) → Ω ¯ + K ¯ Ξ and $$ψ (3770)→ \bar{Ω }^+ \bar{K}Ξ ^*(1530) \;(Ξ ^*(1530)→ π Ξ $$ ψ ( 3770 ) → Ω ¯ + K ¯ Ξ ∗ ( 1530 ) ( Ξ ∗ ( 1530 ) → π Ξ ), and calculate the mass distributions $$\frac{dΓ }{dM_\text {inv}(\bar{K}Ξ )}$$ d Γ d M inv ( K ¯ Ξ ) and $$\frac{dΓ }{dM_\text {inv}(\bar{K}Ξ ^*)}$$ d Γ d M inv ( K ¯ Ξ ∗ ) , respectively. We obtain clear peaks corresponding to the $$Ω (2012)$$ Ω ( 2012 ) . From the decay of $$ψ (3770)→ \bar{Ω }^+ \bar{K}Ξ ^*$$ ψ ( 3770 ) → Ω ¯ + K ¯ Ξ ∗ , we also get a second, broader, peak around $$2035\,\mathrm MeV$$ 2035 M e V , which comes from the $$Ω (2012)$$ Ω ( 2012 ) decay to $$\bar{K}Ξ ^*$$ K ¯ Ξ ∗ . This second peak is closely tied to the molecular picture of the $$Ω (2012)$$ Ω ( 2012 ) with the $$\bar{K}Ξ ^*(1530)$$ K ¯ Ξ ∗ ( 1530 ) and $$η Ω $$ η Ω components. Its observation would provide a boost to the molecular picture of the $$Ω (2012)$$ Ω ( 2012 ) .